PERAN KEPEMIMPINAN DAN PELATIHAN DALAM MENINGKATKAN PRESTASI KERJA (Studi Pada PT Bumi Serpong Damai) - Afrilia, Dwi; Rizqi Fauzi, Mikail Alba; Supratikta, Hadi (Universitas Muhammadiyah Metro, 2024)
Studi ini bertujuan untuk menyelidiki peran yang dimainkan oleh Kepemimpinan dan pelatihan dalam meningkatkan Prestasi Kerja karyawan di perusahaan PT Bumi Serpong Damai. Penelitian akan dilakukan melalui pengumpulan data primer dari karyawan perusahaan Asuransi yang bekerja untuk bagian Customer care sejumlah 45 Pegawai. DaIam riset ini, metode pengambiIan sampeI menggunakan teknik Purposive sampling. Metode anaIisa data yang dipakai iaIah Regression Analysis Menggunakan SPSS 27. Hasil riset menunjukan bahwa Kepemimpinan berpengaruh terhadap Prestasi kerja begitujuga Pelatihan kerja dapat memberikan pengaruh yang positif terhadap Prestasi Kerja. This research is motivated by the low efficiency and effectiveness of employee performance in the Customer Care department at PT Bumi Serpong Damai, which has 45 employees. Leadership and training are considered crucial in enhancing employee performance. The aim of this study is to examine the impact of leadership and training on employee performance in the Customer Care department. Primary data were collected through a survey using purposive sampling and analyzed using regression with SPSS 27. The results show that leadership significantly influences employee performance, with a t-value of 3.800 > t-table 2.018 and a significance value of 0.001 < 0.05. Training also has a significant effect on performance, with a t-value of 2.709 > t-table 2.018 and a significance value of 0.010 < 0.05. The conclusion of this study is that leadership and training are key factors that can improve employee performance in the Customer Care department.